2018
DOI: 10.1182/bloodadvances.2018020123
|View full text |Cite
|
Sign up to set email alerts
|

CD16+ monocytes give rise to CD103+RALDH2+TCF4+ dendritic cells with unique transcriptional and immunological features

Abstract: Classical CD16− vs intermediate/nonclassical CD16+ monocytes differ in their homing potential and biological functions, but whether they differentiate into dendritic cells (DCs) with distinct contributions to immunity against bacterial/viral pathogens remains poorly investigated. Here, we employed a systems biology approach to identify clinically relevant differences between CD16+ and CD16− monocyte-derived DCs (MDDCs). Although both CD16+ and CD16− MDDCs acquire classical immature/mature DC markers in vitro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 108 publications
2
32
0
1
Order By: Relevance
“…DC-like cells can be generated by differentiation of monocytes into monocyte-derived DCs (MDDCs), which can occur in vitro via IL-4 and granulocyte-macrophage colony stimulatory factor (GM-CSF) supplementation or in vivo at tissue sites during inflammation (7779), but whether MDDCs form in circulation during homeostasis is unclear. CD16 + MDDCs generated in vitro express several key genes associated with the DC4s described by Villani et al (14), namely SERPINA1, CD97, ITGAL , and TCF7L2 (80), but CD14 + MDDCs appear to transcriptionally align with CD14 + DCs in skin rather than CD14 + blood monocytes (50). Further fate mapping and lineage tracing studies adopting the exact gating strategy used to describe these subsets would be valuable for confirming their exact ontogeny.…”
Section: Dendritic Cell Subsets and Ontogenymentioning
confidence: 99%
“…DC-like cells can be generated by differentiation of monocytes into monocyte-derived DCs (MDDCs), which can occur in vitro via IL-4 and granulocyte-macrophage colony stimulatory factor (GM-CSF) supplementation or in vivo at tissue sites during inflammation (7779), but whether MDDCs form in circulation during homeostasis is unclear. CD16 + MDDCs generated in vitro express several key genes associated with the DC4s described by Villani et al (14), namely SERPINA1, CD97, ITGAL , and TCF7L2 (80), but CD14 + MDDCs appear to transcriptionally align with CD14 + DCs in skin rather than CD14 + blood monocytes (50). Further fate mapping and lineage tracing studies adopting the exact gating strategy used to describe these subsets would be valuable for confirming their exact ontogeny.…”
Section: Dendritic Cell Subsets and Ontogenymentioning
confidence: 99%
“…It was shown that CHST2 can link the residue to the PSGL1 protein molecule (5). There are additional transferases including CHST15, which similar to CHST2 shows increased mRNA expression in CD16+ monocytes (12) and B3GALT2, which is increased in slan+ compared to slan- CD16+ monocytes (13). These findings need confirmation and the role of these transferases in generating the slan-residue needs to be determined.…”
Section: Cell Surface Phenotype Of Cd16+ Monocytes and Slan+ Cellsmentioning
confidence: 99%
“…Similar findings were reported for CD16 + Mo in the context of SIV infection [28] , with increased CD16 + Mo activation being associated with an increased risk of SIV acquisition in the context of a vaccination trial [29] . Finally, CD16 + and CD16 -Mo differentiate into DC and MΦ with unique molecular features that qualify them as key players in HIV pathogenesis [30][31][32] . While it is well-documented that CD16 + Mo fuel chronic inflammation in HIV/SIV infection, their contribution to HIV reservoir persistence during ART remains unclear.…”
Section: Introductionmentioning
confidence: 99%